Single axis solar tracker: article - Syed Omar, Syed Mohd Harussani (UiTM, 2010)
The Single Axis Solar Tracker is created to track the maximum sun daily. This project is invented especially to prevent wasting energy during sunrise to sunset. This project is needed because it can increase maximum power produced daily using photo-voltaic Nowadays there are many trackers available in market but most of them cost a lot, wasting so much energy such as wasting energy on motor since the power require to rotate the photo-voltaic module is high and very complicated design. The operation of this project is the tracker will move automatically from east to west daily. To completely specify the position of the sun it is necessary to specify three coordinates. However, if one assumes the distance from the sun to the Earth to be constant, the position of the sun can be specified using two coordinates. Two common choices are the solar altitude and the azimuth. The purpose of this project is to compare the power output produced by using tracker and fixed angle. This project use programmable interface controller (PIC) for controlling the tracker